Halogen Chemistry of Hydrothermal Micas: a Possible Geochemical Tool in Vectoring to Ore for Porphyry Copper-Gold Deposit - Idrus, Arifudin (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
Porphyry copper-gold deposit commonly exhibits an extensive alteration zone of hydrothermal micas particularly biotite and sericite. This study is aimed to analyze and utilize the chemistry of halogen fluorine and chlorine of biotite and sericite to be a possible tool in vectoring to ore for copper porphyry deposits. To achieve the objectives, several selected altered rock samples were taken crossing the Batu Hijau copper-gold mine from inner to outer of the deposit, and hydrothermal micas contained by the rocks were analyzed petrographically and chemically. Mineral chemistry was detected by electron microprobe analyzer, whilst biotite is petrographically classified as either magmatic or hydrothermal types. Sericite replacing plagioclase occurred as fine-grained mineral and predominantly associated with argillic-related alteration types. Biotites in the Batu Hijau deposit are classified as phlogopite with a relatively low mole fraction magnesium (XMg) (~0.75) compared to the “typical” copper porphyry deposit (~0.82). The relationship between the XMg and halogen contents are generally consistent with “Fe-F and Mg-Cl avoidance rules”.  F content in biotite and sericite decrease systematically from inner part of the deposit which is represented by early biotite (potassic) zone where the main copper-gold hosted, to the outer part of the deposit. However, chlorine in both biotite and sericite from each of the alteration zones shows a relative similar concentration, which suggests that it is not suitable to be used in identification of the alteration zones associated with strong copper-gold mineralization. H2O content of the biotite and sericite also exhibits a systematic increase outward which may also provide a possible geochemical vector to ore for the copper porphyry deposits. This is well correlated with fluorine content of biotite in rocks and bulk concentration of copper from the corresponding rocks.